A method for testing the longitudinal conductivity of a proton exchange membrane

CN117269796BActive Publication Date: 2026-11-03BEIJING SINOHYTEC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311337368.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2026-11-03
Estimated Expiration
2043-10-16

AI Technical Summary

Technical Problem

Existing technologies cannot accurately measure the longitudinal proton conductivity of the proton exchange membrane in membrane electrode assembly testing, leading to inaccurate fuel cell performance evaluation.

Method used

By designing the structure of the membrane electrode assembly and using electrochemical impedance spectroscopy to calculate the longitudinal conductivity of the proton exchange membrane, the longitudinal conductivity of the proton exchange membrane is accurately measured using the formula σ=L/RWT and the resistance difference of membrane electrode assemblies with different thicknesses.

Benefits of technology

This method enables accurate measurement of the longitudinal conductivity of the proton exchange membrane under actual membrane electrode assembly testing conditions, thereby improving the accuracy of fuel cell performance evaluation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117269796B_ABST
    Figure CN117269796B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of fuel cell, in particular to a kind of proton exchange membrane longitudinal conductivity test method.The present application provides a kind of proton exchange membrane longitudinal conductivity test method, comprising the following steps: electrochemical impedance test is carried out to first membrane electrode assembly and second membrane electrode assembly, and the longitudinal conductivity of proton exchange membrane is obtained after calculation;Wherein, the first membrane electrode assembly includes three layers of proton exchange membrane;The second membrane electrode assembly includes a layer of proton exchange membrane.The longitudinal conductivity test method of proton exchange membrane provided by the present application can accurately measure the longitudinal proton conductivity of the proton exchange membrane in the membrane electrode assembly under the actual membrane electrode test conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fuel cell technology, and in particular to a method for testing the longitudinal conductivity of a proton exchange membrane. Background Technology

[0002] Proton exchange membrane fuel cells (PEMFCs) typically use hydrogen as fuel, directly converting chemical energy into electrical energy through an electrochemical reaction. PEMFCs are highly efficient, low-pollution, and noiseless energy conversion devices. The membrane electrode assembly (MEA) is a key component of the PEMFC, serving as the site of electrochemical reactions, energy conversion, and multiphase mass transport. The proton exchange membrane is a solid organic thin film composed of ionomers that conducts protons, insulates the anode and cathode, and blocks reactant gases from the anode and cathode. The proton exchange membrane is the core of the MEA, and its research and development are of great significance.

[0003] The proton exchange membrane (PEM) used in proton exchange membrane fuel cells must possess good mechanical properties and high proton conductivity. For currently commercially available PEMs, the main tests are stability, gas permeability, durability, and proton conductivity. As a key factor determining the performance of the PEM, proton conductivity determines the energy output and operating voltage of the fuel cell.

[0004] During the electrochemical testing of the membrane electrode assembly, the high-frequency impedance under electrochemical impedance spectroscopy (EIS) testing is obtained, which is assumed to be the proton exchange membrane resistance; or, by testing proton exchange membranes of different thicknesses, a linear relationship is obtained for extrapolation; or, the proton resistance and electronic resistance are decomposed through an electrochemical testing model.

[0005] As a product, a membrane electrode assembly requires material selection for its proton exchange membrane component. However, the resistance obtained from electrochemical testing of a membrane electrode assembly is a holistic measurement and cannot be precisely broken down to the proton exchange membrane resistance (which is assumed to be half of the high-frequency resistance). In the membrane electrode structure, the proton exchange membrane is located in the middle, and the measured high-frequency impedance of the membrane includes the contact resistance of each layer. Therefore, it is impossible to obtain the longitudinal proton conductivity of the proton exchange membrane from the membrane electrode testing.

[0006] In view of this, the present invention is hereby proposed. Summary of the Invention

[0007] The purpose of this invention is to provide a method for testing the longitudinal conductivity of a proton exchange membrane, which can accurately measure the longitudinal proton conductivity of the proton exchange membrane in a membrane electrode assembly under actual membrane electrode testing conditions.

[0008] To achieve the above-mentioned objectives of this invention, the following technical solution is adopted:

[0009] This invention provides a method for testing the longitudinal conductivity of a proton exchange membrane, comprising the following steps:

[0010] Electrochemical impedance spectroscopy was performed on the first and second membrane electrode assemblies, and the longitudinal conductivity of the proton exchange membrane was calculated.

[0011] The first membrane electrode assembly includes three layers of proton exchange membrane; the second membrane electrode assembly includes one layer of proton exchange membrane.

[0012] Furthermore, the method for testing the longitudinal conductivity of a proton exchange membrane includes the following steps:

[0013] S1. Perform an electrochemical impedance test on the first membrane electrode assembly to obtain the resistance of the first membrane electrode assembly;

[0014] S2. Perform an electrochemical impedance spectroscopy test on the second membrane electrode assembly to obtain its resistance:

[0015] S3. Calculate the longitudinal conductivity of the proton exchange membrane using the formula σ = L / RWT; where σ is the proton conductivity (S / cm); L is the thickness of the proton exchange membrane (cm); R is the resistance of the proton exchange membrane (Ω); W is the width of the proton exchange membrane (cm); T is the length of the proton exchange membrane (cm); R = (R1 - R2) / 2; R1 is the resistance of the first membrane electrode assembly (Ω); R2 is the resistance of the second membrane electrode assembly (Ω).

[0016] Furthermore, the first membrane electrode assembly includes a cathode catalyst coating, a first proton exchange membrane, a second proton exchange membrane, a third proton exchange membrane, and an anode catalyst coating arranged sequentially.

[0017] Furthermore, the method for fabricating the first membrane electrode assembly includes the following steps:

[0018] The cathode catalyst coating is hot-pressed onto the surface of the first proton exchange membrane to obtain the first composite membrane;

[0019] The anolyte catalyst coating is hot-pressed onto the surface of the third proton exchange membrane to obtain the second composite membrane;

[0020] The first composite membrane, the second proton exchange membrane, and the second composite membrane are stacked sequentially and then hot-pressed to obtain the first membrane electrode assembly.

[0021] Furthermore, the temperature of the hot pressing transfer is 130–150 °C, and the pressure is 0.8–1 MPa;

[0022] And / or, the hot pressing transfer time is 1 to 3 minutes.

[0023] Furthermore, the second membrane electrode assembly includes a cathode catalyst coating, a fourth proton exchange membrane, and an anode catalyst coating arranged sequentially.

[0024] Furthermore, the cathode catalyst coating comprises a platinum-carbon catalyst and a polymer proton conductor.

[0025] Furthermore, the anode catalyst coating comprises a platinum-carbon catalyst and a polymer proton conductor.

[0026] Furthermore, the conditions for the electrochemical impedance test are: temperature of 60–80℃, pressure of 130–160 kPa, bias voltage of 0.1–0.2 V, frequency of 10 kHz–1 Hz, and AC amplitude voltage of 1.5–2.5 mV.

[0027] Furthermore, the conditions for the electrochemical impedance test are: temperature 75℃, pressure 150kPa, bias voltage 0.15V, frequency 10kHz~1Hz, and AC amplitude voltage 2mV.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0029] The method for testing the longitudinal conductivity of proton exchange membranes provided by this invention designs the structure and fabrication process of the membrane electrode assembly to form a comparative experiment. Using mature electrochemical impedance spectroscopy (EIS) testing, the longitudinal conductivity of the proton exchange membrane in the membrane electrode assembly can be accurately measured under actual membrane electrode assembly testing conditions. Attached Figure Description

[0030] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0031] Figure 1 This is a schematic diagram of the hot-pressing transfer of the cathode catalyst coating of the present invention onto the surface of the first proton exchange membrane.

[0032] Figure 2 This is a schematic diagram of the hot-pressing transfer of the anodic catalyst coating of the present invention onto the surface of the third proton exchange membrane.

[0033] Figure 3 This is a schematic diagram of the preparation method of the first membrane electrode assembly of the present invention.

[0034] Figure 4The above are electrochemical impedance spectroscopy results for the first and second membrane electrode assemblies of this invention. Detailed Implementation

[0035] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0036] The following is a detailed description of a method for testing the longitudinal conductivity of a proton exchange membrane according to an embodiment of the present invention.

[0037] In some embodiments of the present invention, a method for testing the longitudinal conductivity of a proton exchange membrane is provided, comprising the following steps:

[0038] Electrochemical impedance spectroscopy was performed on the first and second membrane electrode assemblies, and the longitudinal conductivity of the proton exchange membrane was calculated.

[0039] The first membrane electrode assembly includes three layers of proton exchange membrane; the second membrane electrode assembly includes one layer of proton exchange membrane.

[0040] Proton exchange membrane fuel cells (PEMFCs) use proton exchange membranes (PEMs) as electrolytes. The performance of the PEM directly affects the cell performance, energy efficiency, and lifespan of the PEM. The proton conductivity of the PEM is an important indicator for evaluating the performance of the PEM.

[0041] Longitudinal conductivity is the conductivity along the direction parallel to the surface of the proton exchange membrane. Longitudinal conductivity reflects the ability of protons to be conducted longitudinally.

[0042] The method for testing the longitudinal conductivity of proton exchange membranes provided by this invention designs a comparative experiment based on the structure and preparation method of the membrane electrode assembly; using mature electrochemical impedance spectroscopy (EIS) testing, the longitudinal proton conductivity of the proton exchange membrane in the membrane electrode assembly can be accurately measured under actual membrane electrode assembly testing conditions.

[0043] In some embodiments of the present invention, the method for testing the longitudinal conductivity of a proton exchange membrane specifically includes the following steps:

[0044] S1. Perform electrochemical impedance spectroscopy on the first membrane electrode assembly to obtain the resistance of the first membrane electrode assembly;

[0045] S2. Perform electrochemical impedance spectroscopy on the second membrane electrode assembly to obtain its resistance:

[0046] S3. Calculate the longitudinal conductivity of the proton exchange membrane using the formula σ = L / RWT; where σ is the proton conductivity (S / cm); L is the thickness of the proton exchange membrane (cm); R is the resistance of the proton exchange membrane (Ω); W is the width of the proton exchange membrane (cm); T is the length of the proton exchange membrane (cm); R = (R1 - R2) / 2; R1 is the resistance of the first membrane electrode assembly (Ω); R2 is the resistance of the second membrane electrode assembly (Ω).

[0047] The first membrane electrode assembly was subjected to EIS testing to obtain an EIS curve, and the resistance R1 of the first membrane electrode assembly was obtained, which is the resistance of the three-layer proton exchange membrane. The second membrane electrode assembly was subjected to EIS testing to obtain an EIS curve, and the resistance R2 of the second membrane electrode assembly was obtained, which is the resistance of the one-layer proton exchange membrane. The difference between the resistance R1 of the first membrane electrode assembly and the resistance R2 of the second membrane electrode assembly is the resistance of the two-layer proton exchange membrane. Half of the resistance of the two-layer proton exchange membrane is the resistance of the proton exchange membrane. Then, the longitudinal conductivity of the proton exchange membrane was calculated using the formula σ=L / RWT.

[0048] In some embodiments of the present invention, the first membrane electrode assembly includes a cathode catalyst coating, a first proton exchange membrane, a second proton exchange membrane, a third proton exchange membrane, and an anode catalyst coating arranged sequentially.

[0049] See Figure 1 , Figure 2 and Figure 3 In some embodiments of the present invention, the method for preparing the first membrane electrode assembly includes the following steps:

[0050] The cathode catalyst coating is hot-pressed onto the surface of the first proton exchange membrane to obtain the first composite membrane;

[0051] The anolyte catalyst coating is hot-pressed onto the surface of the third proton exchange membrane to obtain the second composite membrane;

[0052] After stacking the first composite membrane, the second proton exchange membrane, and the second composite membrane in sequence, hot pressing is performed to obtain the membrane electrode assembly.

[0053] In some embodiments of the present invention, a first composite membrane, a second proton exchange membrane, and a second composite membrane are stacked sequentially, with the cathode catalyst coating in the first composite membrane located on the side away from the second proton membrane, and the anode catalyst coating in the second composite membrane located on the side away from the second proton membrane.

[0054] In some specific embodiments of the present invention, the method for preparing the membrane electrode assembly includes the following steps:

[0055] S1. The cathode catalyst coating with the first protective film is hot-pressed and transferred to the surface of the first proton exchange membrane to obtain the first composite membrane;

[0056] S2. The anode catalyst coating with the second protective film is hot-pressed and transferred to the surface of the third proton exchange membrane to obtain the second composite membrane;

[0057] S3. Following the order of the first protective film, cathode catalyst coating, first proton exchange membrane, second proton exchange membrane, third proton exchange membrane, anode catalyst coating, and second protective film, the first composite membrane, second proton exchange membrane, and second composite membrane are stacked sequentially, subjected to hot pressing, the first and second protective films are peeled off, and double-sided frame plastic sealing is performed to obtain the membrane electrode assembly.

[0058] In some embodiments of the present invention, the first protective film and the second protective film comprise polytetrafluoroethylene (PTFE) films.

[0059] In some embodiments of the present invention, in the method for preparing the first membrane electrode assembly, the temperature of hot pressing transfer is 130–150°C, and the pressure is 0.8–1 MPa; typically, but not limitingly, for example, the temperature of hot pressing transfer can be a range of 130°C, 135°C, 140°C, 145°C, 150°C, or any combination thereof; the pressure of hot pressing transfer can be a range of 0.8 MPa, 0.85 MPa, 0.9 MPa, 0.95 MPa, 1 MPa, or any combination thereof.

[0060] In some embodiments of the present invention, in the method for preparing the first membrane electrode assembly, the hot pressing transfer time is independently 1 to 3 minutes; typically, but not limitingly, for example, the hot pressing transfer time can be a range of 1 minute, 2 minutes, 3 minutes, or any combination thereof.

[0061] In some embodiments of the present invention, the second membrane electrode assembly includes a cathode catalyst coating, a fourth proton exchange membrane, and an anode catalyst coating arranged sequentially.

[0062] In some embodiments of the present invention, the method for preparing the second membrane electrode assembly includes the following steps:

[0063] The cathode catalyst coating and the anode catalyst coating are respectively attached to the surface of the fourth proton exchange membrane to obtain the second membrane electrode assembly.

[0064] In the method for testing the longitudinal conductivity of the proton exchange membrane of the present invention, the proton exchange membranes used are all the same; that is, the first proton exchange membrane, the second proton exchange membrane, the third proton exchange membrane, and the fourth proton exchange membrane are the same.

[0065] In some embodiments of the present invention, the cathode catalyst coating comprises a platinum-carbon catalyst and a polymer proton conductor.

[0066] In some embodiments of the present invention, the thickness of the cathode catalyst coating is 7 to 15 μm; typically, but not limitingly, for example, the thickness of the cathode catalyst coating can be a range of 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or any combination thereof.

[0067] In some embodiments of the present invention, the anode catalyst coating comprises a platinum-carbon catalyst and a polymer proton conductor.

[0068] In some embodiments of the present invention, the thickness of the anodic catalyst coating is 2 to 5 μm; typically, but not limitingly, for example, the thickness of the anodic catalyst coating can be a range of 2 μm, 3 μm, 4 μm, 5 μm or any combination thereof.

[0069] In some embodiments of the present invention, the proton exchange membrane includes, but is not limited to, any one of perfluorosulfonic acid proton exchange membranes, partially fluorinated polymer membranes, non-fluorinated polymer membranes, composite membranes, and hydrocarbon membranes.

[0070] In some embodiments of the present invention, the conditions for electrochemical impedance spectroscopy are as follows:

[0071] The temperature is 60–80℃, the pressure is 130–160 kPa, the bias voltage is 0.1–0.2 V, the frequency is 10 kHz–1 Hz, and the AC amplitude voltage is 1.5–2.5 mV.

[0072] In some embodiments of the present invention, the conditions for electrochemical impedance spectroscopy are as follows:

[0073] The temperature is 75℃, the pressure is 150kpa, the bias voltage is 0.15V, the frequency is 10kHz~1Hz, the AC amplitude voltage is 2mV, the gas is hydrogen or nitrogen, and the humidity is 100%RH.

[0074] Example 1

[0075] The method for testing the longitudinal conductivity of a proton exchange membrane provided in this embodiment includes the following steps:

[0076] S1. Perform electrochemical impedance spectroscopy (EIS) on the first membrane electrode assembly to obtain the resistance of the three-layer proton exchange membrane;

[0077] S2. Perform electrochemical impedance spectroscopy (EIS) on the second membrane electrode assembly to obtain the resistance of a proton exchange membrane.

[0078] S3. The longitudinal conductivity of the proton exchange membrane is obtained by subtracting the resistance of the first proton exchange membrane from the resistance of the three-layer proton exchange membrane.

[0079] The method for preparing the first membrane electrode assembly includes the following steps:

[0080] The cathode catalyst coating (composed of platinum carbon catalyst and polymer proton conductor with a thickness of 7-15 μm) with PTFE membrane was hot-pressed onto the surface of the first proton exchange membrane. The hot-pressing conditions were: temperature 140℃, pressure 0.9 MPa, and time 2 min, to obtain the first composite membrane.

[0081] The anodic catalyst coating (composed of platinum carbon catalyst and polymer proton conductor with a thickness of 2-5 μm) with PTFE membrane was hot-pressed onto the surface of the third proton exchange membrane. The hot-pressing conditions were: temperature 140℃, pressure 0.9 MPa, and time 2 min, to obtain the second composite membrane.

[0082] Following the sequence of PTFE membrane, cathode catalyst coating, first proton exchange membrane, second proton exchange membrane, third proton exchange membrane, anode catalyst coating, and PTFE membrane, the first composite membrane, second proton exchange membrane, and second composite membrane are stacked sequentially, and then hot-pressed for transfer. The hot-pressing conditions are: temperature 140℃, pressure 0.9MPa, and time 2min. After peeling off the PTFE membrane, double-sided frame sealing is performed to obtain the first membrane electrode assembly.

[0083] The method for preparing the second membrane electrode assembly includes the following steps:

[0084] The cathode catalyst coating (composed of platinum-carbon catalyst and polymer proton conductor, with a thickness of 7–15 μm) and the anode catalyst coating (composed of platinum-carbon catalyst and polymer proton conductor, with a thickness of 2–5 μm) are respectively attached to the surface of the fourth proton exchange membrane to obtain the second membrane electrode assembly.

[0085] The conditions for EIS testing are shown in Table 1:

[0086] Table 1

[0087] temperature 75℃ pressure 150kPa / 150kPa (Anode / Cathode) gas <![CDATA[H2 / N2]]> humidity 100% RH / 100% RH (Anode / Cathode) bias voltage 0.15V frequency 10kHz~1Hz AC amplitude voltage 2mV

[0088] The formula for calculating proton conductivity is: σ = L / RWT;

[0089] In the formula, σ is the proton conductivity, in S / cm; L is the thickness of the proton exchange membrane, in cm; R is the resistance of the proton exchange membrane, in Ω; W is the width of the proton exchange membrane, in cm; T is the length of the proton exchange membrane, in cm; R=(R1-R2) / 2; R1 is the resistance of the first membrane electrode assembly, in Ω; R2 is the resistance of the second membrane electrode assembly, in Ω.

[0090] The longitudinal conductivity of the proton exchange membrane (perfluorosulfonic acid resin and ePTFE) measured using the test method of this embodiment is 0.078 S / cm.

[0091] The electrochemical impedance test results of the first and second membrane electrode assemblies are as follows: Figure 4 As shown.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for testing the longitudinal conductivity of a proton exchange membrane, characterized in that, Includes the following steps: Electrochemical impedance spectroscopy was performed on the first and second membrane electrode assemblies, and the longitudinal conductivity of the proton exchange membrane was calculated. S1. Perform an electrochemical impedance test on the first membrane electrode assembly to obtain the resistance of the first membrane electrode assembly; S2. Perform an electrochemical impedance spectroscopy test on the second membrane electrode assembly to obtain the resistance of the second membrane electrode assembly; S3. Calculate the longitudinal conductivity of the proton exchange membrane using the formula σ=L / RWT; where σ is the proton conductivity (S / cm); L is the thickness of the proton exchange membrane (cm); R is the resistance of the proton exchange membrane (Ω); W is the width of the proton exchange membrane (cm); T is the length of the proton exchange membrane (cm); R=(R1-R2) / 2; R1 is the resistance of the first membrane electrode assembly (Ω); R2 is the resistance of the second membrane electrode assembly (Ω). The first membrane electrode assembly includes three layers of proton exchange membrane; the second membrane electrode assembly includes one layer of proton exchange membrane. The first membrane electrode assembly includes a cathode catalyst coating, a first proton exchange membrane, a second proton exchange membrane, a third proton exchange membrane, and an anode catalyst coating arranged sequentially. The second membrane electrode assembly includes a cathode catalyst coating, a fourth proton exchange membrane, and an anode catalyst coating arranged sequentially.

2. The method for testing the longitudinal conductivity of a proton exchange membrane according to claim 1, characterized in that, The method for preparing the first membrane electrode assembly includes the following steps: The cathode catalyst coating is hot-pressed onto the surface of the first proton exchange membrane to obtain the first composite membrane; The anode catalyst coating is hot-pressed onto the surface of the third proton exchange membrane to obtain the second composite membrane; The first composite membrane, the second proton exchange membrane, and the second composite membrane are stacked sequentially and then hot-pressed to obtain the first membrane electrode assembly.

3. The method for testing the longitudinal conductivity of a proton exchange membrane according to claim 2, characterized in that, The temperature for the hot pressing transfer is 130~150℃, and the pressure is 0.8~1MPa; And / or, the hot pressing transfer time is 1~3 minutes.

4. The method for testing the longitudinal conductivity of a proton exchange membrane according to claim 1, characterized in that, The cathode catalyst coating comprises a platinum-carbon catalyst and a polymer proton conductor.

5. The method for testing the longitudinal conductivity of a proton exchange membrane according to claim 1, characterized in that, The anode catalyst coating comprises a platinum-carbon catalyst and a polymer proton conductor.

6. The method for testing the longitudinal conductivity of a proton exchange membrane according to claim 1, characterized in that, The conditions for the electrochemical impedance spectroscopy test are: temperature 60~80℃, pressure 130~160kPa, bias voltage 0.1~0.2V, frequency 10kHz~1Hz, and AC amplitude voltage 1.5~2.5mV.

7. The method for testing the longitudinal conductivity of a proton exchange membrane according to claim 1, characterized in that, The conditions for the electrochemical impedance spectroscopy test are: temperature 75℃, pressure 150kPa, bias voltage 0.15V, frequency 10kHz~1Hz, and AC amplitude voltage 2mV.

Citation Information

Patent Citations

  • Device and method for testing electric conductivity of powder material and impedance of membrane electrode

    CN103149439A

  • Fuel cell membrane electrode assembly and preparation method thereof

    CN115579497A